Designing full-scale biodigestion plants for the treatment of vinasse in sugarcane biorefineries: How phase separation and alkalinization impact biogas and electricity production costs? - Fuess, Lucas Tadeu; de Araï¿½jo Jï¿½nior, Moacir Messias; Garcia, Marcelo Loureiro [UNESP]; Zaiat, Marcelo (Elsevier, 2017)
Anaerobic digestion (AD) is the most suitable approach for the management of vinasse in sugarcane distilleries because both environmental adequacy and bioenergy recovery could be achieved through biogas production. Because the literature lacks data on the implementation and operation of full-scale AD plants for enhanced energy recovery from vinasse, this study presents different designs for AD plants applied to vinasse in large-scale distilleries, considering both single- and two-phase schemes and different alkalizing strategies. Investment and operating costs and biogas and electricity production costs were obtained for each case. The results indicate that phase separation is economically feasible when scaling up AD plants in biorefineries. Despite the higher capital and operating costs in such schemes, the estimated biogas and electricity production costs reached equivalent or lower values compared with those of single-phase AD layouts, depending on the alkalizing strategy used. With respect to the alkalizing strategy, the best results were associated with sodium hydroxide dosing and/or effluent recirculation, with electricity costs reaching values 1.8- to 2.3-fold lower than grid electricity. In contrast, the competitive use of sodium bicarbonate in AD plants for treating vinasse requires further dosing optimization.
Keywords: Economic feasibility; Ethanol biorefinery; Full-scale biodigestion; Phase separation; Vinasse management